2004
DOI: 10.1093/cercor/bhg091
|View full text |Cite
|
Sign up to set email alerts
|

MEG Tomography of Human Cortex and Brainstem Activity in Waking and REM Sleep Saccades

Abstract: We recorded the magnetoencephalographic (MEG) signal from three subjects before, during and after eye movements cued to a tone, self-paced, awake and during rapid eye movement (REM) sleep. During sleep we recorded the MEG signal throughout the night together with electroencephalographic (EEG) and electromyographic (EMG) channels to construct a hypnogram. While awake, just prior to and during eye movements, the expected well time-locked physiological activations were imaged in pontine regions, with early 3 s pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 50 publications
12
112
0
2
Order By: Relevance
“…Therefore, it is plausible that the onset time of the BOLD response actually precedes REM onset. However, considering the hemodynamic delay between neural activity and the onset of the corresponding BOLD response (typically 1-2 s) and the recent MEG/EEG studies that reported neural activities immediately before REMs in the several brain areas including the anterior cingulate cortex, parahippocampal gyrus, amygdala and so on (Ioannides et al 2004;Abe et al 2008), we cannot fully eliminate the possibility that neural activities not only in the PGO areas but also in other activated areas start just before REM onset. Even in that case, there were signiWcantly large diVerences in the onset time between the PGO areas and other cortical/subcortical areas.…”
Section: Activation Accompanying Remmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, it is plausible that the onset time of the BOLD response actually precedes REM onset. However, considering the hemodynamic delay between neural activity and the onset of the corresponding BOLD response (typically 1-2 s) and the recent MEG/EEG studies that reported neural activities immediately before REMs in the several brain areas including the anterior cingulate cortex, parahippocampal gyrus, amygdala and so on (Ioannides et al 2004;Abe et al 2008), we cannot fully eliminate the possibility that neural activities not only in the PGO areas but also in other activated areas start just before REM onset. Even in that case, there were signiWcantly large diVerences in the onset time between the PGO areas and other cortical/subcortical areas.…”
Section: Activation Accompanying Remmentioning
confidence: 96%
“…A number of imaging and psychophysiological studies have addressed this issue using a variety of investigative approaches in humans. Electroencephalography (EEG) and magnetoencephalography (MEG) studies have found REM-related neural activity in the visual cortex where no such activity was seen after waking saccades in total darkness (Miyauchi et al 1990;Ioannides et al 2004;Ogawa et al 2005). However, the exact location of this activity is still unclear, partly because the inverse problem of estimating the current sources on the basis of EEG/MEG data alone is fundamentally ill-posed, and partly because the deep structural resolution of EEG/MEG is variable (Baillet et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human neuroimaging studies reveal that rapid eye movements (REMs) during REM sleep are closely associated with transient activity in limbic regions such as the amygdala and parahippocampal gyrus (Abe, Ogawa, Nittono, & Hori, 2004;Ioannides et al, 2004).…”
Section: The Role Of Rem Sleep and Amygdala Function In Emotional Memorymentioning
confidence: 99%
“…Typically, bursts of pontine waves are associated with REMS. Several observations suggest that PGO waves also occur during human sleep [123][124][125][126][127][128]. In rats, the density of pontine waves during post-training REMS is proportional to the gain in performance to an avoidance task [129].…”
Section: Rems and Pontine Wavesmentioning
confidence: 99%